Molecular patterns of isolated tubulitis differ from tubulitis with interstitial inflammation in early indication biopsies of kidney allografts - Hruba, Petra; Madill-Thomsen, Katelynn; Mackova, Martina; Klema, Jiri; Maluskova, Jana; Voska, Ludek; Parikova, Alena; Slatinska, Janka; Halloran, Philip F; Viklicky, Ondrej (Scientific reports, 2020)
The Banff 2019 kidney allograft pathology update excluded isolated tubulitis without interstitial inflammation (ISO-T) from the category of borderline (suspicious) for acute T cell-mediated rejection due to its proposed benign clinical outcome. In this study, we explored the molecular assessment of ISO-T. ISO-T or interstitial inflammation with tubulitis (I + T) was diagnosed in indication biopsies within the first 14 postoperative days. The molecular phenotype of ISO-T was compared to I + T either by using RNA sequencing (n = 16) or by Molecular Microscope Diagnostic System (MMDx, n = 51). RNA sequencing showed lower expression of genes related to interferon-y (p = 1.5 *10-16), cytokine signaling (p = 2.1 *10-20) and inflammatory response (p = 1.0*10-13) in the ISO-T group than in I + T group. Transcripts with increased expression in the I + T group overlapped significantly with previously described pathogenesis-based transcript sets associated with cytotoxic and effector T cell transcripts, and with T cell-mediated rejection (TCMR). MMDx classified 25/32 (78%) ISO-T biopsies and 12/19 (63%) I + T biopsies as no-rejection. ISO-T had significantly lower MMDx scores for interstitial inflammation (p = 0.014), tubulitis (p = 0.035) and TCMR (p = 0.016) compared to I + T. Fewer molecular signals of inflammation in isolated tubulitis suggest that this is also a benign phenotype on a molecular level.
Keywords: Nephritis, Interstitial; Biopsy; Humans; Graft Rejection; Female; přežívání štěpu; lidé; Biomarkers; alografty; výpočetní biologie; biopsie; Computational Biology; transplantace ledvin; biologické markery; ženské pohlaví; Male; stanovení celkové genové exprese; transkriptom; vysoce účinné nukleotidové sekvenování; Kidney Transplantation; intersticiální nefritida; Transcriptome; High-Throughput Nucleotide Sequencing; Allografts; Gene Expression Profiling; mužské pohlaví; Graft Survival; rejekce štěpu